Improved polymerase ribozyme efficiency on hydrophobic assemblies - Müller, Ulrich F. (Cold Spring Harbor Laboratory Press, 2008)
During an early step in the evolution of life, RNA served both as genome and as catalyst, according to the RNA world hypothesis. For self-replication, the RNA organisms must have contained an RNA that catalyzes RNA polymerization. As a first step toward recapitulating an RNA world in the laboratory, a polymerase ribozyme was generated previously by in vitro evolution and design. However, the efficiency of this ribozyme is about 100-fold too low for self-replication because of a low affinity of the ribozyme to its primer/template substrate. To improve the substrate interactions by colocalizing ribozyme and substrate on micelles, we attached hydrophobic anchors to both RNAs. We show here that the hydrophobic anchors led to aggregates with the expected size of the corresponding micelles. The micelle formation increased the polymerization yield of full-length products by 3- to 20-fold, depending on substrates and reaction conditions. With the best-characterized substrate, the improvement in polymerization efficiency was primarily due to reduced sequence-specific stalling on partially extended substrates. We discuss how, during the origin of life, micellar ribozyme aggregates could have acted as precursors to membrane-encapsulated life forms.